Investigação bio-eletroquímica do metronidazol e seus derivados - Boane, Anastácio Armando (2015)
This work investigates the electrochemical behavior, the correlation between the potential of the first reduction peak with giardicidal activity, as well as the interaction with DNA of metronidazole (MTZ) and its derivatives, modified in the lateral chain by fluoride (F-MTZ), chloride (Cl-MTZ), azide (N3-MTZ), bromide (Br-MTZ), iodide (I-MTZ), mesyl (Ms-MTZ) and tosyl (Ts-MTZ) groups. The study was performed in aprotic (DMF + TBAPF6) and in aqueous media (phosphate buffer solution pH 7.2 with 20% ethanol) using glassy carbon (GCE) (d = 1 mm) electrode, using electrochemical techniques such as cyclic voltammetry (CV), differential pulse voltammetry (DPV) and square wave voltammetry (SWV). The mechanism for the reduction of MTZ and its derivatives F-MTZ, Cl-MTZ, N3-MTZ, at 0.100 V s-1 is typical of nitroaromatic compounds and occurs in two stages, the first is monoelectronic, with a reversible nature, corresponding to the nitro anion radical formation, followed by a more pronounced wave at more negative potential, irreversible and multi-electronic which probably leads to the formation of nitroso derivative and other products with extended reduction. The analogues Br-MTZ, I-MTZ, Ms-MTZ and Ts-MTZ, with strong leaving groups, present the first reduction peaks without their anodic counterparts, which are more intense than the second ones, a typical behavior of dissociative electron transfer, an EC process (electron transfer followed by a irreversible chemical reaction). In this medium, the facility of reduction of the eight substrates represented by the reduction potential of the first wave (EpIc) follows the order: I-MTZ > Cl-MTZ > Ts-MTZ > Br-MTZ > Ms-MTZ > N3-MTZ > F-MTZ > MTZ showing an easier redution for derivatives with strong leaving groups. This finding shows correlation with biological activity, mainly against Giardia lamblia. In protic medium, the reduction mechanism is, as expected, entirely different, being characterized by only one irreversible well-defined reduction peak at less cathodic potentials than in aprotic medium, which corresponds to the formation of hydroxylamine when 4 e-/4 H+ are consumed. We also investigated the interaction of the compounds with DNA. MTZ showed a slight interaction with dsDNA by UV-Vis spectroscopy in phosphate buffer pH 7.2 with 20% ethanol. Using DPV at a GCE (d = 3 mm), in acetate buffer, pH 4.5, with 20% ethanol, it was found that practically no interaction occurs between the eight compounds with the film of dsDNA. After electrochemical reduction of the compounds, at adequate cathodic potentials, interaction with the dsDNA film was evidenced, with the presence of the diagnostic anodic peaks at potentials typical of guanine and adenine bases. A different behavior was evidenced in ssDNA solution. All the nitrocompounds interact with ssDNA, even without the step of reductive pre-conditioning, however, the interaction is more intense after reduction. Decrease and shifts of the peak potential of ssDNA towards more positive values are observed. These facts suggest that DNA might be a potential target for these biologically active compounds.